Straightforward Synthesis of Novel 4-Styrylquinolines/4-Styrylquinolin-2-ones and 9-Styryldihydroacridin-1(2H)-ones from Substituted 2′-Aminochalcones - Meléndez, Angie; Plata, Esteban; Rodríguez, Diego; Ardila, Diana; Guerrero, Sergio A.; Acosta, Lina M.; Cobo, Justo; Nogueras, Manuel; Palma, Alirio (Synthesis, 2020)
An alternative and efficient one-step approach to develop small libraries of polysubstituted 4-styrylquinolines/4-styrylquinolin-2-ones and 9-styryldihydroacridin-1-ones is described. According to this approach, new series of these compounds were straightforwardly synthesized in high yields starting from synthetically available 2′-aminochalcones and 1,3-dicarbonyl compounds in glacial acetic acid as a catalyst via the Friedländer reaction. Our approach also offers an expeditious way to access novel molecular hybrids in whose structures styryl and chalcone fragments are attached at the C4 and C3 positions, respectively, of the quinoline ring. All synthesized compounds were fully characterized by means of IR, HRMS and NMR techniques, and most were screened at the National Cancer Institute, USA, for their antitumor activity.
Keywords: 4-styrylquinolines; Friedländer reaction; 2′-aminochalcones; quinoline–chalcone hybrids; Claisen–Schmidt condensation